2018
DOI: 10.1063/1.5011368
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic luminescence and core structure of freshly introduced a-screw dislocations in n-GaN

Abstract: Dislocations introduced by the scratching or by the indentation of the basal and prismatic surfaces of low-ohmic unintentionally n-type doped GaN crystals were investigated by means of cathodoluminescence and transmission electron microscopy (TEM). A strong luminescence of straight segments of a-screw dislocations was observed in the temperature range of 70–420 K. The spectrum of dislocation related luminescence (DRL) consisted of a doublet of narrow lines red shifted by about 0.3 eV with respect to the band g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 48 publications
7
33
0
Order By: Relevance
“…The absence of dark contrasts of half‐loops in the basal plane indicates that the dislocation motion proceeded in a prismatic glide system only. Low‐temperature CL measurements confirmed that spectral properties of these dislocations were the same as the ones of dislocations introduced by scratching or indentation described earlier . Photoluminescence (PL) spectra of dislocation‐rich and dislocation‐free regions in the range from 3.5 eV (near band edge emission, NBE) to 3 eV coincided well with each other and are not shown here.…”
supporting
confidence: 79%
See 4 more Smart Citations
“…The absence of dark contrasts of half‐loops in the basal plane indicates that the dislocation motion proceeded in a prismatic glide system only. Low‐temperature CL measurements confirmed that spectral properties of these dislocations were the same as the ones of dislocations introduced by scratching or indentation described earlier . Photoluminescence (PL) spectra of dislocation‐rich and dislocation‐free regions in the range from 3.5 eV (near band edge emission, NBE) to 3 eV coincided well with each other and are not shown here.…”
supporting
confidence: 79%
“…A dislocation‐related PL spectrum at 5 K consists of very narrow Lorenz‐type DRL H line at 3.167 eV with a full width at half maximum (FWHM) around 0.5–0.7 meV and of a broader DRL L line at 3.134 eV with FWHM of around 2.6–3 meV. The energy separation between DRL H and DRL L peaks is about 33 meV, which coincides well with the CL‐spectra value at temperatures higher than 70 K . PL intensity of DRL H at 5 K was 5–10 times higher than the intensity of DRL L .…”
supporting
confidence: 75%
See 3 more Smart Citations